The Realization of Apologies by Indonesian Speaking in Indonesian and English as a Foreign Language - Fitratul Illahi; Hamzah Hamzah (Universitas Negeri Padang, 2023)
Interlanguage Pragmatics examines how people with different first languages and cultural backgrounds use a common language system during social interactions. This research aimed to examine apology strategies employed by native speakers of Indonesia and Indonesian learners of English as a Foreign Language (EFL). A total of 40 people took part in the study, 20 native speakers of Indonesia and 20 learners of Indonesian as a foreign language (EFL). The study utilized a Discourse Completion Test (DCT) consisting of 6 different situations. The data were analyzed using the Banikalef (2015) methodology, which was obtained from the Olshtain and Cohen (1983) framework. The data demonstrate that they employ different strategies when offering apologies. Some of these strategies are IFID, explanation of account, acknowledgement of responsibility, offer of repairs, denial of responsibility, and concern for the hearer. It analyses the correlation between the utilization of politeness in social factors, such as power and social distance. Furthermore, gender differences cannot be overlooked.